Cognitive and emotional states detection and visualization in learning through developing learner agency in smart environments (International Journal of Food and Nutritional Sciences, 2019)
Learner agency is nothing but learning on own and gaining ownership on learning as well. According to Cury, Dlliotm DA Fonsecam Moller, 2006 students who believe that perform better in IQ tests than students who believe intelligence is invariable. This learner agency direct to the learner’s own interested goals desires and skills so the expected outcomes are positive as learners are able to direct their own choice based learning. As per the national research council with student agency are positively related to college and career outcomes because students are able to direct their own learning and transfer the knowledge they learned in the class room to new settings. Implementation of Learning Agency in K L deemed to be university the computer based training programs based learning in order to augment the challenging capacity of learners to get succeeded, collaborative and communicated and involved in world around them. The teachers who acted as facilitators in a computer based training based programs in order to enrich and empowers with refined strategies to support learner community.